Mosquito-borne viruses circulating in Kinshasa, Democratic Republic of the Congo - Mbanzulu, Kennedy Makola (Int J Infect Dis, 2017)
BACKGROUND: Diseases caused by mosquito-borne viruses are among the most important emerging diseases that threaten human and animal health, particularly in Africa. However, little attention has been paid to these diseases in the Democratic Republic of the Congo (DRC). The present cross-sectional study was undertaken between March and May 2014 to investigate the presence of mosquito-borne viruses in mosquitoes collected from five municipalities of Kinshasa, DRC. METHODS: Mosquitoes were collected using BG-Sentinel traps and battery-powered aspirators. Female mosquitoes were pooled according to their genera and sampling locations, preserved in RNAlater, and later screened for viruses using reverse transcription PCR (RT-PCR) assays. RESULTS: A total of 2922 mosquitoes were collected and 29 pools of female mosquitoes, containing approximately 30 mosquitoes each, were tested. Twelve of the 29 (41.4%) mosquito pools were found to be infected with at least one arbovirus, with eight (27.5%) pools positive for Alphavirus, nine (31%) for Flavivirus, and five (17.2%) for Bunyaviridae. Chikungunya, o’nyong’nyong, and Rift valley fever viruses were detected. CONCLUSIONS: The present study shows that mosquitoes in Kinshasa carry mosquito-borne viruses that may have serious public health implications. Further investigations on the presence of mosquito-borne viruses in the human and livestock populations of Kinshasa and DRC are recommended.